Hubungan Lama Penggunaan Kontrasepsi Iud terhadap Efek Samping IUD pada Akseptor IUD di Puskesmas Sudiang Kota Makassar - Ratna, Ratna; Kasim, Jasmila; Termature, Ardolof Steny (Jurnal Kebidanan Mutiara Mahakam, 2020)
IUD (Intra Uterine Device) is a contraception device that is inserted into the uterus, made of plastic material, some are wrapped with copper, and the shape is various. A common form and perhaps widely known by society is the form of a spiral. The purpose of this research is to know the relationship between the length of IUD use of side effects on IUD acceptor in the Sudiang Public Health Center in Makassar City. The design of the research used is quantitative descriptic research with the approach method that is in use is cross sectional. Sampling using accidental sampling with 58 respondents. Data collection is done using questionnaires and being embraced with a Chi square test (P < 0.05). The results of the study showed obtained a P value of 0034 where Î± 0.05 which means p. < Î± 0.05 that there is a relationship between the length of use of IUD with the side effects of IUD on the acceptor in the Sudiang Public Health Center in Makassar City. It was concluded that there was a meaningful relationship between the length of use of IUD with side effects on IUD acceptor at Sudianag Public Health Center in Makassar City , where older users have more mild side effects and less experienced side effects of weight whereas New users are experiencing more severe side effects and fewer mild side effects